(untitled) (Research, Society and Development, 2020)
The objective was to reflect on the therapeutic environment and behaviors of hypertensive patients in Primary Care. Descriptive qualitative research with a theoretical foundation in Roy’s adaptive model, carried out in a Primary Care Unit in Minas Gerais, Brazil, with 30 hypertensive participants. Sociodemographic characterization data were collected and individual in-depth interviews were conducted, with guiding questions, recorded, between August and October 2019. Data treatment with content analysis carried out with the support of SPSS version 24 and NVivo Pro11® software. Theoretical density (Pearson ≥0.7). All ethical and legal aspects of research were met. The therapeutic environment was understood by the participants as a component of their daily relationships in the professional / user dyad, due to their dependence on the use of primary care services, given their current health condition. It is concluded that the control of stimuli, coping mechanisms and ineffective behaviors require more attention by nurses.